The Influence of Teachers’ Attitude Towards the Students’ Motivation in EFL Class - Tiara Alamsyah Putri; Martriwati Martriwati (Jurnal Studi Guru dan Pembelajaran, 2025)
This study aims to explicitly investigate how teachers’ attitudes comprising cognitive, affective, and behavioral components influence students’ motivation in English as a Foreign Language (EFL) classrooms in Indonesia. The study employed a quantitative, correlational design and involved 300 senior high school students from grades X to XII around Jabodetabek. The participants were selected using convenience sampling techniques. Data were gathered using a structured four-point Likert scale questionnaire adapted from validated instruments: for teacher attitude and for student motivation. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that teachers’ attitudes significantly influence students’ motivation (R² = 0.388; β = 0.623; T = 12.205; p < 0.000). The results underscore the importance of fostering a supportive, respectful, and emotionally intelligent teaching atmosphere to increase student engagement in EFL learning. These findings contribute to theory building in the Indonesian EFL context and offer practical implications for teacher training programs.